PENGUKURAN PARAMETER FISIKA-KIMIA PADA BUDIDAYA KARAMBA DI SUNGAI TONDANO, KELURAHAN TERNATE, KOTA MANADO - Robert J. Rompas (EKOTON, 2012)
A research of water quality for the life of aquaculture in karamba, this research aims to get analysis of physic and chemistry parameter including: temperature, humidity, DO, pH, NH3, H2S dan (PO4). The technique of sampling has been done amount two times with the interval time of two weeks at the two stations and the time of taking in the morning, afternoon, and evening to analyze temperature parameter, humidity, DO and pH done directly and analysis of parameter NH3, H2S and PO4 use Automatic Absorption Spectrophotometer. Generally the result of water quality analysis at the aquaculture still under the limitation for activity of aquaculture.